Mental ill-health among health and social care professionals: an analysis using administrative data - Emma Curran; Michael Rosato; Finola Ferry; Gerard Leavey (International Journal of Population Data Science, 2021)
Objective Health and Social Care (HSC) workers are at high risk of job-related stress, burnout and mental ill-health. This study examines differences in self-reported mental health and psychotropic medication uptake across HSC occupational groups.